Meningkatkan Kemampuan Mengenal Huruf Abjad Melalui Media Jepitan Huruf bagi Anak Disabilitas Intelektual Ringan (Single Subject Research Kelas III di SLB Kemala Bhayangkari) - susanti, iis; Zulmiyetri, Zulmiyetri; Rahmahtrisilvia, Rahmahtrisilvia; Arisulmahdi, Arisulmahdi (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to improve letter recognition skills in a child with mild intellectual disability in the 3rd grade of SLB Kemala Bhayangkari Tanah Datar, specifically in recognizing letters A to J. The subject of the study is KF, a young boy with mild intellectual disability who has difficulties in independently recognizing letters of the alphabet. The method used is quantitative research with an experimental approach in the form of Single Subject Research (SSR) using an A-B design. Letter clip media is used as the independent variable (X), while the ability to recognize letters of the alphabet is the dependent variable (Y). Data collection was conducted through direct observation and recording the subject's ability to recognize letters in the baseline condition (A) before the intervention and after the application of letter clip media (B). Data analysis was performed quantitatively descriptive by comparing the percentage of mastery of the alphabet letters in both conditions. The results showed a significant increase in the ability to recognize alphabet letters in the subjects, with a mastery percentage of 35% in the baseline condition increasing to 90% in the intervention condition. These findings indicate that the use of letter clip media is effective in helping children with mild intellectual disabilities to enhance their ability to recognize alphabet letters.